Analysis of Customer Satisfaction Levels with Sharia Banking Services at BSI Bener Meriah - Wahyuni Wahyuni; Muhammad Doli Harahap; Muhammad Lathief Ilhamy Nasution (Penerbit Jurnal Indonesia, 2022)
This article aims to determine the level of customer satisfaction with sharia banking services at Bsi Bener Meriah. Facing an increasingly critical society like now, apart from products, the services provided also affect the sustainability of the company. maintain customer trust and satisfaction with their services. Service as the first promotion to prospective customers, if the quality of service is excellent, then the customer will continue to transact, and vice versa.